Genetic Determinants of Virulence and Antimicrobial Resistance in Shigella species.: A Comprehensive Review on Virulence Genes, Resistance Mechanisms, and Horizontal Gene Transfer - Issa, Aldhahi Hasan; Shaker, Maad Naser (American Journal of Biology and Natural Sciences, 2025)
Shigella spp. are among the enteric pathogens of great morbidity and mortality all over the world particularly in developing countries. Once it has established pathogenesis, a typical large complex array of virulence genes found within chromosomal islands and large virulence plasmids encode invasion proteins, secretion apparatuses,and regulatory factors involved in pathogenesis by epithelial cell invasion plus immune evasion. High prevalence rates of parallel alarming multidrug-resistant (MDR) Shigella strains pose an immediate public health hazard due to complications in treatment and increased risks for outbreaks. This review pauses at the major genetic factors that are associated with Shigella virulence about the ipaH, virF, mxi-spa, and icsA gene clusters. It further reviews at a molecular level how resistance is achieved in Shigella towards antibiotics drawing resistance genes including blaTEM, aadA, tetA, and qnr among many others that are also usually found on plasmids, transposons as well as integrons. Conjugation, transformation, and transduction are horizontal gene transfer (HGT) mechanisms described as means by which resistance plus virulence determinants can very fastly move not only within populations of Shigella but also other populations of enteric pathogens. Synthesizing recent findings, meanwhile emphasizing the dire need to carry out genomic surveillance, therapeutic strategy recalibration, and an antibiotic stewardship program to battle against the evolving genetic landscape of Shigella would be fruitful. The relationship between virulence and resistance interacting at the genetic level must be understood for further research initiatives, clinical management, and vaccine development.